Analisis Vitamin C Pada Buah Rambusa (Passiflora foetida L.) - Karmila Karmila; Siti Nuryanti (Media Eksakta, 2021)
The rambusa plant (Passiflorafoetida L) grows wild and vines. The fruit is small round green when it is raw and light yellow when the fruit is ripe. Rambusa fruit contains useful substances for improving people's nutrition, one of them is vitamin C which is needed by human as a source of antioxidants. This study aimed to determine the levels of vitamin C in raw and riperambusa fruit extracts. The vitamin C levels were analysed by iodimetric titration. The results obtained vitamin C levels in raw rambusa fruit was 1.31 mg/g and in the ripe was 2.21 mg/g, respectively. This data shows that vitamin C levels in rambusa fruit increase based on the level of maturity.